Development of a Smart Bioink for Bioprinting Applications - Montero, Félix E.; Rezende, Rodrigo A.; da Silva, Jorge V. L.; Sabino, Marcos A. (Frontiers in Mechanical Engineering, 2019)
Biofabrication is an incipient and fast-growing field of research that continues to develop groundbreaking innovations. Considerable progress has also been made in additive manufacturing technologies, which are used for the production of complex geometry using biomaterials, such as scaffolds and, most recently, bioink-based structures. Some of the topics related to these new breakthroughs in tissue engineering and bioprinting will be discussed. Additionally, the obtained experimental results in this work contribute to the recent advances in such sciences. Formulations of sodium alginate (NaAlg)/Poly(N-Isopropylacrylamide) (PNIPAm)/ZnSO4-based smart bioinks were developed and characterized. The lower critical solution temperature (LCST), viscosity and thermal stability were determined through UV-Visible spectroscopy, a rheological analysis and a thermogravimetric analysis (TGA), respectively. Furthermore, an injectability test was performed in order to assess the influence of the extrusion process in the morphology of the bioinks like scaffolds (after lyophilization) using scanning electron microscopy SEM. According to the obtained results, the scaffolds presented a structure composed of interconnected pore systems, which were affected by the presence of the Zn2+ ion, and the extrusion process. The biocompatibility of the gels was tested through a hemolysis assay using erythrocytes and the obtained results indicate that have not cytotoxic effects. For all these reasons these formulations are candidates for the obtention of intelligent bioinks applicable for bioprinting and tissue engineering.